Sustainability : life chances and livelihoods - Redclift, M. R. (Routledge, 2000)
Annotation The concept of sustainability is traditionally viewed in exclusively environmental terms. Sustainability: Life Chances and Livelihoods links peoples livelihoods and life chances to the concept of sustainability by examining the way in which social and economic processes complement and compound environmental change. Looking at the main ingredients of sustainable development - health, economic policy, land use, ethics and education, in both the north and south, this book demonstrates the way in which the life chances of individuals both effect and are affected by, their environments. Sustainability: Life Chances and Livelihoods shows that the scope of sustainability thinking needs to be widened to embrace public policies and experiences in both developed and developing countries. By providing a comparative focus, both spatially and temporally, the contributors demonstrate how the environmental concerns of the northern developed world are culturally translated into the south, often into immediate survival questions.